Policies to clean up toxic industrial contaminated sites of Gela and Priolo: a cost-benefit analysis - Cairns John; Bianchi Fabrizio; Guerriero Carla; Cori Liliana (BMC, 2011)
Abstract Background Cost-benefit analysis is a transparent tool to inform policy makers about the potential effect of regulatory interventions, nevertheless its use to evaluate clean-up interventions in polluted industrial sites is limited. The two industrial areas of Gela and Priolo in Italy were declared "at high risk of environmental crisis" in 1990. Since then little has been done to clean the polluted sites and reduce the health outcomes attributable to pollution exposure. This study, aims to quantify the monetary benefits resulting from clean-up interventions in the contaminated sites of Gela and Priolo. Methods A damage function approach was used to estimate the number of health outcomes attributable to industrial pollution exposure. Extensive one way analyses and probabilistic analyses were conducted to investigate the sensitivity of results to different model assumptions. Results It has been estimated that, on average, 47 cases of premature death, 281 cases of cancer and 2,702 cases of non-cancer hospital admission could be avoided each year by removing environmental exposure in these two areas. Assuming a 20 year cessation lag and a 4% discount rate we calculate that the potential monetary benefit of removing industrial pollution is €3,592 million in Priolo and €6,639 million in Gela. Conclusions Given the annual number of health outcomes attributable to pollution exposure the effective clean-up of Gela and Priolo should be prioritised. This study suggests that clean-up policies costing up to €6,639 million in Gela and €3,592 million in Priolo would be cost beneficial. These two amounts are notably higher than the funds allocated thus far to clean up the two sites, €127.4 million in Gela and €774.5 million in Priolo, implying that further economic investments - even considerable ones - could still prove cost beneficial.